Optimal scheduling of clean energy storage and charging integrated system by fusing DE algorithm and kernel search algorithm - Wang, Xinhua; Jia, Yujie; Su, Hao; Dang, Hua; Lu, Songfu (Energy Informatics, 2025)
In the context of rapid developments in artificial intelligence and the clean energy industry, the optimal scheduling of clean energy storage and charging systems has become increasingly prominent. This study proposes an optimal scheduling method that integrates Differential Evolution (DE) and Kernel Search Optimization (KSO) algorithms. By incorporating DE’s mutation, crossover, and selection operations into the KSO framework, the method effectively avoids local optima while retaining KSO’s advantages in handling complex structures and large-scale data. Experimental results demonstrate that the convergence speed of the fusion algorithm is improved by 34.2%, 30.8%, 28.6%, and 23.4% over four other algorithms for hybrid functions, and by 56.7%, 52.9%, 25.3%, and 21.4% for combined functions. Additionally, the utilization of renewable energy increased from 40% to nearly 70% within 24 h. It can be seen that the convergence speed and renewable energy utilization of the fusion algorithm are significantly improved compared with the four baseline methods, highlighting its effectiveness in large-scale clean energy systems. This research provides an effective scheduling strategy for optimizing clean energy storage and charging systems. This study provides an effective scheduling strategy for optimizing clean energy storage and charging systems, and supports scalable and efficient energy management of urban and rural energy grids. The results show that the optimization of the integrated charging system can not only achieve optimal scheduling in a shorter time, but also reduce operating costs and resource waste, and effectively improve the overall operating efficiency of the energy system. Research to promote the efficient use of renewable energy will help reduce dependence on fossil fuels, thereby reducing greenhouse gas emissions and environmental pollution, which will have a positive impact on achieving the Sustainable Development goals and addressing climate change, and promote a win-win situation for the economy and the environment.